Three-jet production in diffractive deep inelastic scattering at HERA - Chekanov, S; Derrick, M; Krakauer, D; Magill, S; Musgrave, B; Pellegrino, A; Repond, J; Yoshida, R; Mattingly, M; Antonioli, P; Bari, G; Basile, M; et al. (2001)
Three-jet production in the reaction ep → eXp has been studied with the ZEUS detector at HERA using an integrated luminosity of 42.74 pb-1.The data were measured in the kinematic region 5 < Q2 < 100 GeV2, 200 < W < 250 GeV and 23 < MX < 40 GeV. The diffractive signal was selected by requiring a large rapidity gap in the outgoing proton direction. Jets were reconstructed in the centre-of-mass system of X using the exclusive kT-algorithm. A sample of three-jet events in diffraction has been identified. Differential cross sections were measured as a function of the jet pseudorapidity and jet transverse momentum with respect to the virtual photon-pomeron axis. The jets going in the pomeron direction are broader than those going in the virtual-photon direction. This is consistent with models predicting that gluons are predominantly produced in the pomeron direction and quarks in the virtual-photon direction. © 2001 Elsevier Science B.V. All rights reserved.